Recovery of critical metals from waste promotes green technologies. (Research'eu results magazine)
Recycling plays a vital role in the drive towards a more sustainable society by reducing the amount of waste going to landfill thereby conserving natural resources. An EU-funded initiative has therefore developed innovative processes using powerful solvents to recycle metals from unwanted electrical and electronic material.